PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX - Ahmad Ridha; Muhammad Asran; Edy Kurniawan (STKIP Subang, 2026)
Kuliah Kerja Nyata Pendidikan (KKN-DIK) activities represent a form of student community service focused on enhancing learning quality in schools. This research aims to improve mathematics learning outcomes for ninth-grade students through the implementation of the Problem Based Learning (PBL) model. The activity was conducted at UPT SMPN 1 Polongbangkeng Utara, Takalar Regency, involving 32 students from class IX.1 as research subjects. The Classroom Action Research (PTK) method was employed over two cycles, encompassing planning, implementation, observation, and reflection stages. Data were collected via classroom process observations and student learning outcome evaluations. Results indicate that the PBL model successfully increased student engagement during learning and significantly improved mathematics learning outcomes across attitude, knowledge, and skills aspects. Thus, Problem Based Learning serves as an innovative alternative to optimize mathematics learning in KKN-DIK programs.